Differences of salivary urea levels in plaque-induced gingivitis and periodontally healthy patients in Periodontology Clinic of The Faculty of Dentistry North Sumatera University (USU) Medan - Aini H. Nasution; Saipriaya S. Babu (Journal of Dentomaxillofacial Science, 2018)
Objective: This study aims to know the difference of urea levels in saliva of plaque-induced gingivitis patients and in healthy patients at the Periodontology Clinic of Faculty of Dentistry USU.Material and Methods: This analytical study used a spectrophotometer to see urea levels in 30 salivary samples of gingivitis patients and healthy patients.Results: Â After the samples were analyzed, it was found that the urea level in saliva of gingivitis patients was higher with the mean score of 52.062 g/dL whereas the urea level in saliva of healthy patients was 26.614 g/dL. The results of this study are in line with several studies conducted using various methods and samples.Conclusion: The urea level in saliva of plaque-induced gingivitis patients was significantly higher when compared with healthy patients.